Implementation of an Agent System to Increase Manufacturing Process Efficiency in a Smart Factory - Nugroho, Budi; Pasaribu, Hiras; Oscar, Schersclight (Journal of Computer Science Advancements, 2024)
The rapid advancement of Industry 4.0 technologies has transformed traditional manufacturing into highly interconnected smart factory systems. However, achieving optimal efficiency in such environments remains challenging due to complex production flows and the need for real-time decision-making. This study explores the implementation of an agent-based system to improve efficiency within a smart factory setting, focusing on how autonomous agents can manage, coordinate, and optimize manufacturing processes. The research aims to analyze the effectiveness of agent systems in reducing production delays, enhancing resource allocation, and improving overall productivity. A combination of simulation and experimental analysis was employed to assess the impact of agent-based solutions on production efficiency. The agent system was integrated into the smart factory model, where agents performed tasks such as process monitoring, predictive maintenance scheduling, and dynamic resource management. Results indicate that the agent system contributed to a 15% reduction in idle time, a 20% improvement in machine utilization, and an overall increase in production throughput. These improvements highlight the potential of agent systems to address inefficiencies in manufacturing by enabling adaptive and autonomous decision-making processes. The findings suggest that agent-based systems are viable solutions for enhancing operational efficiency in smart factories, paving the way for further innovations in automated manufacturing environments. Implementing such systems could lead to more resilient, responsive, and efficient manufacturing processes, ultimately supporting the broader adoption of smart factory practices in the industry.